Pengembangan Model Pembelajaran Responsif Gender di PAUD Ainina Mejobo Kudus (THUFULA, 2013)
One that perpetuates gender inequality is education at various levels.Then break ing the early gender bias chain through gender responsive learningat Pre-school (PAUD) on the agenda are not inevitable. Manipulating genderresponsive learning can be taught in two aspects: teaching materials and teachinglearning process. The subject matter development is done by inserting a gender quality message into the subject matter. While the development of teaching and learning activities is carried out since teachers set instructional design models to the classroom learning implementation process. They are packaged so that thegender equality implementation could be realized.